Analysis of consumer demand for traceable pork in China based on a real choice experiment. Issue 2 (5th May 2015) - Wu, Linhai; Wang, Hongsha; Zhu, Dian
Abstract : Purpose: – The purpose of this paper is to reveal the actual consumer demand for traceable pork by investigating consumer preferences for pork with combined levels of traceability information based on differences in individual consumer preferences, in order to support the government in decision making regarding the gradual construction of safe food markets. Design/methodology/approach: – Combinations of four types of traceability information, including farming, slaughter and processing, distribution and sales, and government certification, with price were randomly designed. To identify consumer preferences for these attribute combinations of traceable pork, 215 consumers in Wuxi, Jiangsu Province were investigated using a real choice experiment and the mixed logit model. Findings: – Significant heterogeneity was observed in consumer preferences for traceable pork. The information of farming, slaughter and processing, distribution and marketing, and government certification could significantly improve consumer utility. Moreover, consumers had the highest preference for government certification information. Originality/value: – Although numerous studies have been performed on consumer preferences for food safety attributes using a real choice experiment, almost none of them focus on Chinese consumers. Therefore, this study is an attempt to fill this gap. The conclusions of this study can serve as a reference for the Chinese government in developing safe food consumption policies. Although Chinese consumers have cried out for improvement of pork safety, they have different preferences for traceability information; thus, the government must promote traceable food step-by-step, using consumer preferences as a starting point.